2016
DOI: 10.1371/journal.pone.0153590
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism Disorder Is Associated with Pulmonary Tuberculosis in Individuals with Respiratory Symptoms from Brazil

Abstract: BackgroundDiabetes mellitus (DM) has been associated with increased risk for pulmonary tuberculosis (PTB) in endemic settings but it is unknown whether PTB risk is also increased by pre-DM. Here, we prospectively examined the association between glucose metabolism disorder (GMD) and PTB in patients with respiratory symptoms at a tuberculosis primary care reference center in Brazil.MethodsOral glucose tolerance test was performed and levels of fasting plasma glucose and glycohemoglobin (HbA1c) were measured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
27
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 28 publications
7
27
0
10
Order By: Relevance
“…Again, discrepancies driven by epidemiologic, clinical and even microbiologic factors may explain the conflicting findings. Despite the differences in clinical presentation, several studies reported similar results to those reported here, showing increased mycobacterial loads in sputum smears in hyperglycemic vs. normoglycemic patients [11,13,[26][27][28][29]. A multinational, harmonized, clinical study is necessary to formally demonstrate the effect of DM and/or PDM on TB disease presentation and to test if such effect is independent on the bacterial loads in sputum.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Again, discrepancies driven by epidemiologic, clinical and even microbiologic factors may explain the conflicting findings. Despite the differences in clinical presentation, several studies reported similar results to those reported here, showing increased mycobacterial loads in sputum smears in hyperglycemic vs. normoglycemic patients [11,13,[26][27][28][29]. A multinational, harmonized, clinical study is necessary to formally demonstrate the effect of DM and/or PDM on TB disease presentation and to test if such effect is independent on the bacterial loads in sputum.…”
Section: Discussionsupporting
confidence: 74%
“…We have previously reported that patients with hyperglycemia more frequently present with multiple TBrelated symptoms compared to those with normoglycemia [11]. In addition, TB-DM patients more commonly required transfer from a primary care center to hospitals in order to have access to more complex care [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PDM has been shown recently to be associated with an increased risk of latent TB infection [7], to be associated with pulmonary TB in individuals with respiratory symptoms [8], and to be associated with dysregulated cytokine responses in pulmonary TB [9]. In addition, the prevalence of PDM has been reported to be as high as 25% in individuals with active TB [10].…”
Section: Introductionmentioning
confidence: 99%